The Phenomenon of Financing and its Social Effects. Brief Analysis of the Colombian Case (Revista cientifica In Vestigium Ire, 2019)
This research aims to show how the phenomenon of Financialization has been developing, and the role that this phenomenon played in the economic crisis of 1970 and the one that began in 2007. Likewise, observe how, within this process, the pursuit of profits has led to the reification of consumers who are increasingly submerged within the financial system through the different products offered by the market, which hasled to asocial- economic imbalance; process in which Colombia has not been alienated, being affected also in its economic structure and in its social system. The better knowledge of this situation will favor the more responsible development of the sector, as well as the adoption of measures that could improve the situation without suppressing a brake on economic growth.
Keywords: Financing; Banking; Consumption; Social Impact; Sector Regulation